Effect of integrated nutrient management (INM) on growth and quality attributes of kharif onion (Allium cepa L.) (Indian Journal of Arid Horticulture, 2016)
Onion (Allium cepa L.) is a bulbous biennial herb belonging to the family Alliaceae. Often referred to as the "Queen of the kitchen," onion is used throughout the year in salads, condiments, and as a cooking ingredient with other vegetables. The pungency of onion is attributed to the sulfur compound "allyl propyl disulfide" found in its volatile oil, while the outer skin's color is due to "quercetin" (Nadkarni, 1954). Onion bulbs are rich in minerals such as phosphorus (50 mg/100g), iron (0.7 mg/100g), and calcium (18 mg/100g), as well as carbohydrates (11.0 g/100g), protein (1.2 g/100g), vitamins C (11 mg/100g), fibers (0.6 g/100g), and nicotinic acid (0.4 mg/100g) (Aykroyd, 1963). The productivity of onion in India is relatively low (16.81 t ha^-1) compared to other countries, highlighting the need for standardized integrated nutrient management (INM) to enhance production in light-textured soils. Kharif season production of onion is crucial for ensuring a continuous year-round supply. Organic manures enhance the production of polysaccharides and other compounds that improve soil structure, tilth, aeration, moisture movement, and retention (Bose et al., 2001). The inoculation of bio-fertilizers such as Azospirillum and PSB has been shown to improve vegetative growth and increase yield by 10-30 percent (Mohondas, 1999; Tilak and Annapurna, 1993). This study investigates the effects of organic manures, inorganic fertilizers, and bio-fertilizers on kharif onion grown in loamy sand soil.
Keywords: nutrient; polysaccharides; loamy sand soil